Theory of the evolution of superconductivity in Sr2RuO4 under anisotropic strain - Yuan-Chun Liu (Nature Portfolio, 2017)
Condensed matter physics: strain drives evolution of superconductivity Intriguing superconducting properties appear upon anisotropic strain applied, with an insight revealed by the change of electronic structure. Yuan-Chun Liu and colleagues at the Nanjing University and collaborators in China and Switzerland studied the superconductivity and competing orders in Sr2RuO4 under strain using functional renormalization group theory. An enhancement of superconducting transition temperature T c followed by a sudden drop can be traced from the evolution of Fermi surface, the contour of zero-energy excitations in momentum space in the single-particle band structure, and the development of a competing spin-density-wave order. In consistent with recent experiments, the results provide an understanding of the strain-driven superconductivity evolution by means of Fermi surface change. This work not only helps to reveal the microscopic origin behind the effect of strain on superconductivity, but also offers a solution toward manipulating superconductivity.